Feminist Geography Unbound : Discomfort, Bodies, and Prefigured Futures - Gökarıksel, Banu (Book collections on Project MUSE., 2021)
"Drawing on diverse theoretical backgrounds and a range of field sites, contributors consider how race, gender, citizenship, and class often determine who feels comfort and who is tasked with producing it. They work through bodies as terrains of struggle that make claims to space and enact political change, and they ask how these politics prefigure the futures that we fear or desire. The book also champions feminist geography as practice, through interviews with feminist scholars and interludes in which feminist collectives speak to their experience inhabiting and transforming academic spaces"--